2020
DOI: 10.1177/1477760620977502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano TiO2 particles on the properties of carbon fiber-epoxy composites

Abstract: A composite material was prepared using epoxy as a matrix, and carbon fiber (20% volume fraction) together with nano titanium dioxide (TiO2) particles in varying weight fractions (0,2,4 and 6%) as hybrid reinforcement. Mechanical tests (impact strength and wear resistance) were carried out, in addition to the study of liquid uptake behavior during immersion in chemical solutions, and inspection with scanning electron microscope imaging to reveal the microscopic details. The results showed that the addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…These bubbles have acted as stress concentration spots, besides the effect of the nanoclay low aspect ratio, which contributed to the more insufficient adhesion between nanoclay itself and the two-phase matrix to reduce the values of flexural strength of the composite. 29 This result agrees with Siddiqui et al, who suggested that the drop in flexural strength with increasing nanoclay content may have resulted from the agglomerations, especially at higher weight fractions than 3%, and this may have led to lessening of nanoclay ability as a reinforcement. The random distribution of nanoclay upon the matrix may have also contributed to the decrease in flexural strength as these agglomerations work as stress-concentration sites.…”
Section: Flexural Strengthsupporting
confidence: 91%
“…These bubbles have acted as stress concentration spots, besides the effect of the nanoclay low aspect ratio, which contributed to the more insufficient adhesion between nanoclay itself and the two-phase matrix to reduce the values of flexural strength of the composite. 29 This result agrees with Siddiqui et al, who suggested that the drop in flexural strength with increasing nanoclay content may have resulted from the agglomerations, especially at higher weight fractions than 3%, and this may have led to lessening of nanoclay ability as a reinforcement. The random distribution of nanoclay upon the matrix may have also contributed to the decrease in flexural strength as these agglomerations work as stress-concentration sites.…”
Section: Flexural Strengthsupporting
confidence: 91%
“…However, adding reinforcements-a technique often employed to create wear-resisting composites-can lower the wear rate to a small percentage. Even at minor addition percentages, like the addition of nanoreinforcements and blending epoxy with other polymers, they enhance the protective layer [31].…”
Section: Wear Testmentioning
confidence: 99%
“…There is no statistically significant difference in flexural strength between the reinforced groups and the control group [13]. Impact strength is very important property ,it expressed in terms of the amount of energy absorbed before fracture, and it can calculated by [14]:…”
Section: Introductionmentioning
confidence: 98%